hsa-miR-3177-5p and hsa-miR-3178 Inhibit 5-HT1A Expression by Binding the 3′-UTR Region in vitro - Wu, Xue; Ding, Mei; Liu, Yi; Xia, Xi; Xu, Feng-ling; Yao, Jun; Wang, Bao-jie (Frontiers in Molecular Neuroscience, 2019)
Abnormal expression of the 5-HT1A receptor, which is encoded by the HTR1A gene, leads to susceptibilities to neuropsychiatric disorders such as depression, anxiety, and schizophrenia. miRNAs regulate gene expression by recognizing the 3'-UTR region of mRNA. This study evaluated the miRNAs that might identify and subsequently determine the regulatory mechanism of HTR1A gene. Using the HEK-293, U87, SK-N-SH and SH-SY5Y cell lines, we determined the functional sequence of the 3’-UTR region of the HTR1A gene and predicted miRNA binding. Dual luciferase reporter assay and Western Blot were used to confirm the effect of miRNA mimics and inhibitors on endogenous 5-HT1A receptors. In all cell lines, gene expression of the -17 bp--+443 bp fragment containing the complete sequence of the 3'-UTR region was significantly decreased, although mRNA quantification was not different. The +375 bp--+443 bp sequence, which exhibited the most significant change in relative chemiluminescence intensity, was recognized by hsa-miR-3177-5p and hsa-miR-3178. In HEK-293 and U87 cells, hsa-miR-3177-5p significantly inhibited the 5-HT1A receptor expression, while a hsa-miR-3178 inhibitor up-regulated HTR1A gene expression in SK-N-SH and SH-SY5Y cells. By constructing the pmirGLO-vector with the mutated HTR1A gene, we further confirmed that hsa-miR-3177-5p recognized the HTR1A gene tgtacaca at +377 bp--+384 bp, and the +392 bp--+399 bp fragment cgcgccca was identified by hsa-miR-3178. Hsa-miR-3177-5p and hsa-miR-3178 had significant inhibitory effects on expression of the HTR1A gene and 5-HT1A receptor and may directly participate in the development of neuropsychiatric diseases.